Determinants and resource use efficiency of "better cotton": An innovative cleaner production alternative. (10th November 2017) - Zulfiqar, Farhad; Datta, Avishek; Thapa, Gopal B.
Abstract: The resource constraints along with socioeconomic attributes and capabilities of farmers cause variations in the adoption of agricultural technologies. These variations represent an inefficiency source in complete utilization of management practices and epitomize a lack of achieving full potential offered by "better cotton" – an innovative cleaner production alternative. Therefore, this research focused on identifying the potential areas of improvement in "better cotton" farmers' input use by investigating the technical and economic efficiencies as well as the factors determining the resource use efficiency. Technical, allocative, and economic efficiencies of "better cotton" were analyzed using input-oriented data envelopment analysis. Factors affecting technical and economic efficiencies were identified using bootstrapped truncated regression. There was variation in technical efficiency and it was positively influenced by farmers' education, farming experience, and drainage status, whereas it was negatively influenced by the number of household members involved in farming and the area under cotton. The mean economic efficiency of 56% indicated that at the current productivity level inefficient farmers can reduce their costs by 44%. The economic efficiency was negatively affected by the number of household members involved in farming and the intensity of using crop management practices. Thus, efforts should be made to improve input use efficiency of particularly those "better cotton" farmers who are currently operating inefficiently. This efficiency analysis aims to provide recommendations to policy makers and promoters of "better cotton" as to which practices and inputs should be focused while implementing "better cotton" as a cleaner alternative to conventional cotton. Highlights: This research assessed resource use efficiency of "better cotton" (BC) production. It also analyzed the determinants of technical and economic efficiencies of cotton. The mean technical and economic efficiencies were 79 and 56%, respectively. The allocative inefficiency was a bigger problem than technical inefficiency. BC farmers can further improve their financial returns by using inputs efficiently.